Grouped SPME Comparison of Floral Scent as a Method of Unlocking Phylogenetic Patterns in Volatiles - Latinovic, Adelina; Nichols, David S.; Adams, Vanessa M.; McQuillan, Peter B. (Frontiers in Ecology and Evolution, 2022)
Global crop production rate has exceeded the availability of pollination services provided by managed honeybees, and habitat loss remains a key factor in the loss of wild pollinators. Revegetation of agricultural land and wild pollination may provide a solution; however, the collection of floral trait data that are correlated to pollinator preferences remains an under studied and complex process. Here, we demonstrate a method for scent analysis, ordination [non-metric dimensional scaling (NMDS)], and clustering outputs that provides a fast and reproducible procedure for a broad grouping of flora based on scent and unlocking characteristic inter-floral patterns. We report the floral profiles of 15 unstudied native Australian plant species and the extent to which they match the commonly cultivated seed crops of Daucus carota L and Brassica rapa L. Through solid-phase microextraction (SPME) paired with gas chromatography–mass spectrometry (GC-MS), we identify a set of inter-family shared, common floral volatiles from these plant species as well as unique and characteristic patterns.